2019
DOI: 10.1002/prep.201800279
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sodium Alginate on the Morphology and Properties of High Energy Insensitive Explosive TKX‐50

Abstract: Dihydroxylammonium 5,5′‐bistetrazole‐1,1′‐diolate (TKX‐50) is an energetic ion salt with high energy and low mechanical sensitivity. However, its poor morphology and low binding ability with conventional binders have significantly limited its application. In the present work, we reported a novel strategy to improve the morphology and surface properties of TKX‐50 using sodium alginate (SA) as the modifier by the anti‐solvent method. The results of imaging characterization indicated that SA greatly affected both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…The changing trend of shock wave overpressure with time in Figure 5 is the same as that in the literature [24], indicating that the change curve of air shock wave overpressure with time in each experiment has good repeatability.…”
Section: Variation Of Overpressure Peak Value Of Explosive Shock Wave...supporting
confidence: 78%
“…The changing trend of shock wave overpressure with time in Figure 5 is the same as that in the literature [24], indicating that the change curve of air shock wave overpressure with time in each experiment has good repeatability.…”
Section: Variation Of Overpressure Peak Value Of Explosive Shock Wave...supporting
confidence: 78%
“…[36][37][38] The similar peak patters in SABC spheres as SA, SAB, and SAC implies the successful preparation of g-C 3 N 4 and biochar composite immobilized into alginate. [41][42][43] The above results indicated that the composite possessed a sufficient number of active groups on its surface, which was expected to increase pollutant removal efficiency.…”
Section: Photoelectrochemical Measurementsmentioning
confidence: 75%
“…The rectangular UA crystals are no longer observed in the complexes, which indicates the significant decrease of UA crystallinity. Other studies also find that the morphology of SA complexes can be influenced by the solvent-mediated process …”
Section: Resultsmentioning
confidence: 98%
“…The morphology of UA, carriers, PM, and complexes was observed using a scanning electron microscope (s4800, Hitachi Instruments Co., Ltd., Japan). 40 The powders were fixed on a sample port using carbon double-sided adhesive tape and coated with gold (100 s) using voltages from 10 to 25 kV for scanning to obtain conductive samples.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation